Bimbingan Mahasiswa untuk Membuat Karya Ilmiah sebagai Tugas Akhir Mahasiswa Universitas Terbuka - Bambang Santoso (Jurnal Masyarakat Indonesia (Jumas), 2024)
The community service program for final semester Open University (UT) students aims to enhance their skills in writing scientific papers, a crucial component of their final assignment. Scheduled from April 8, 2024, to May 20, 2024, this initiative focuses on guiding students to adhere to academic writing standards and avoid plagiarism. The overarching goal is to bolster the knowledge and competencies of UT students, positioning them as capable contributors upon graduation. By imparting essential skills in scientific writing, the program seeks to prepare students for success in familial, professional, and social spheres, thereby fostering their leadership potential for the nation's benefit. Employing a dual approach of lectures and hands-on training, the community service endeavors to foster resilient and intellectually adept graduates. The anticipated outcomes include improved academic capabilities and the cultivation of personal attributes conducive to effective professional engagement and societal leadership.